2016
DOI: 10.1002/pbc.26189
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 and TPMT genetic polymorphisms are related to 6‐mercaptopurine intolerance in children treated for acute lymphoblastic leukemia at the Children's Cancer Center of Lebanon

Abstract: This is the first report on the association of TPMT and NUDT15 polymorphisms with MP dose intolerance in Arab patients with ALL. Genotyping for additional polymorphisms may be warranted for potential gene/allele-dose effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 20 publications
3
25
1
1
Order By: Relevance
“…In particular, the NUDT15 variant was most common in East Asians and Hispanics, rare in Europeans, and not observed in Africans, contributing to ethnic differences in 6-MP tolerance [ 14 ]. The incidence of severe myelotoxicity was more frequent in patients with NUDT15 CT or TT genotype, when receiving standard-dose 6-MP therapy, as replicated by other studies [ 21 , 25 27 ]. These results indicate potentially clinical implications of NUDT15 genotyping and comprehensive pharmacogenetic models integrating NUDT15 variants to individualize 6-MP therapy.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…In particular, the NUDT15 variant was most common in East Asians and Hispanics, rare in Europeans, and not observed in Africans, contributing to ethnic differences in 6-MP tolerance [ 14 ]. The incidence of severe myelotoxicity was more frequent in patients with NUDT15 CT or TT genotype, when receiving standard-dose 6-MP therapy, as replicated by other studies [ 21 , 25 27 ]. These results indicate potentially clinical implications of NUDT15 genotyping and comprehensive pharmacogenetic models integrating NUDT15 variants to individualize 6-MP therapy.…”
Section: Introductionsupporting
confidence: 71%
“…The allele frequency of NUDT15 in Chinese children with ALL was 15.7%, which was slightly higher than that found in IBD patients (12.1%) [ 34 ] and Taiwan Chinese children with ALL (11.6%) [ 25 , 35 ] in previous studies. Conversely, the NUDT15 risk allele is less common in other populations, with prevalence of 2% in an admixed American population [ 24 ], 0.4% in Lebanese [ 27 ] and 8.8% in Uruguayan [ 33 ]. In contrast to NUDT15, the overall risk allele frequency of TPMT 719A > G was 2.9% in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, many investigators have been able to replicate these results in studies of thiopurine-treated patients with IBD or ALL 789101112131415161718. In the current study, we successfully established a significant association between NUDT15 p.Arg139Cys and thiopurine-induced leukopenia and severe hair loss.…”
Section: Discussionsupporting
confidence: 56%
“…The high specificity and sensitivity (89.4% and 93.2%, respectively) of NUDT15 p.Arg139Cys recorded by these authors indicate that this variant, rather than TPMT polymorphisms, may be an effective genetic marker for predicting thiopurine-induced adverse events, at least in East Asian populations. To date, this strong association has been confirmed in numerous studies involving subjects with IBD or ALL 789101112131415161718. In addition, a further investigation identified 4 NUDT15 coding variants, including p.Arg139Cys, that influence both nucleotide diphosphatase activity and levels of thiopurine active metabolites, and found loss-of-function NUDT15 variants to be associated with thiopurine intolerance 13.…”
Section: Introductionmentioning
confidence: 74%
“…[ 20 23 ] Besides, other studies in children with acute lymphoblastic leukemia (ALL) have recognized that the NUDT15 R139C variant increased the risk of developing thiopurine-induced toxicity ( P < .00001) and identified a variant in NUDT15 R139C gene to be associated with intolerance of thiopurine dose. [ 17 , 24 26 ] Suzuki et al [ 27 ] found that NUDT15 R139C genotyping could be beneficial in estimating the tolerated dose of 6-MP for Japanese patients with childhood ALL, particularly during the preschool age (younger than 7 years) ( P = .04). Furthermore, the variant frequency of NUDT15 R139C showed ethnic variability: 9.8% in East Asians, 4.1% in Hispanics, 0.2% in Europeans, and 0.0% in Africans.…”
Section: Literature Review and Discussionmentioning
confidence: 99%